The Enclosement of Bolivia and the Argentina Factor - Lacoste, P; Jiménez-Cabrera, D (UNIV ARTURO PRAT, 2016)
The paper examines the role that Argentina had in the enclosure of Bolivia. It considers both its action during the Pacific War, when Bolivia lost its coastline, as during Chilean proposals back out to sea, both in 1895 and 1975. It shows that Bolivia went to Argentina, hoping to gain advantage in their conflicts against Chile. In turn, Argentina drew Bolivia into his influence sphere to pressure Chile, but without assuming strong commitments with that. Subsequently, Chile gave way to Argentina. Once achieved its objectives, Buenos Aires released the hand of Bolivia, which lost the opportunity to recover its access to the sea. The text is of current interest because of the controversy submitted in the International Court of Justice (ICJ), between Bolivia and Chile.